2017
DOI: 10.1111/neup.12410
|View full text |Cite
|
Sign up to set email alerts
|

Marked accumulation of oligodendroglia‐like cells in temporal lobe epilepsy with amygdala enlargement and hippocampal sclerosis

Abstract: Although an increasing number of cases of temporal lobe epilepsy (TLE) with ipsilateral amygdala enlargement (AE) have been reported, there are few pathological reports, and no clear consensus has been established. Oligodendroglia or oligodendroglia-like cells (OLCs) have recently attracted attention in epilepsy studies. Here, we report the clinical and pathological findings of a 40-year-old male TLE patient with AE and hippocampal sclerosis, in whom histopathological study demonstrated remarkable clustering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…There are various reasons why neurons in the brain may acquire epileptogenic properties. In late-onset epilepsy in older people without obvious structural abnormalities, several conditions such as inflammation, autoantibodies, sclerosis, microvascular disorders, and neurodegenerative diseases have been postulated as etiologies [17][18][19][20]. We suspect that in these patients, the abnormal discharges may be caused by the following process: (1) A small number of neurons initiate abnormal discharges due to certain causes/ mechanisms.…”
Section: Interference With the Progression Of Epileptic Pathologymentioning
confidence: 99%
“…There are various reasons why neurons in the brain may acquire epileptogenic properties. In late-onset epilepsy in older people without obvious structural abnormalities, several conditions such as inflammation, autoantibodies, sclerosis, microvascular disorders, and neurodegenerative diseases have been postulated as etiologies [17][18][19][20]. We suspect that in these patients, the abnormal discharges may be caused by the following process: (1) A small number of neurons initiate abnormal discharges due to certain causes/ mechanisms.…”
Section: Interference With the Progression Of Epileptic Pathologymentioning
confidence: 99%
“…83 We also explored evidence of tau pathology in this series, particularly as a previous report identified tau accumulation in glial cells in AE. 84 There is also evidence for neuronal tau accumulation and phosphorylation in the hippocampus and neocortex in TLE with aging, 13 and furthermore, experimental data suggest that tau reduction reduces SUDEP risk in Dravet models. 14 Using three common pTau antibodies in AD research, we noted variable neuronal more than glial accumulation in the amygdala that correlated with the age of patients but not with MRI measures or SUDEP risk factors.…”
Section: Glioneuronal Hamartomamentioning
confidence: 99%
“…However, there is limited information on the underlying pathology of TLE with AE, as only a few cases require surgical intervention. Pathological findings from a small number of surgical cases have included cortical dys-plasia, low-grade glioma, nonspecific gliosis, and accumulation of oligodendroglia-like cells, indicating a heterogeneous disease background [35]. Sone et al [36] found that methionine PET uptake increased in 27% of TLE-AE cases [34].…”
Section: Amygdala Enlargementmentioning
confidence: 99%